2020
DOI: 10.1080/15592324.2020.1774212
|View full text |Cite|
|
Sign up to set email alerts
|

Humic acid improves the physiological and photosynthetic characteristics of millet seedlings under drought stress

Abstract: We aimed to determine whether humic acid (HA) can alleviate the injury of millet caused by drought and its potential mechanism. Millet seeds (Jingu 21 and Zhangza 10) were soaked in different concentrations of HA (0, 50, 10, 200, and 300 mg L −1 ) for 12 h. The physiological and photosynthetic characteristics of millet seedlings, including growth parameters, osmotic regulators, antioxidase activity, photosynthesis, chlorophyll fluorescence, and P700 parameters, were determined before and after drought stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…Furthermore, previous authors [59,[71][72][73] mentioned that HA increased the levels of 40 compounds that are associated with the stress response. HA molecules promote the osmotic adjustment ability, increase leaf water retention, as well the photosynthetic and antioxidant metabolism of plants under drought stress [74,75]. The integration of HA application and a water deficit makes it possible to assess the precision and efficiency of the system in researching the effect of HA on drought tolerance [45,76].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous authors [59,[71][72][73] mentioned that HA increased the levels of 40 compounds that are associated with the stress response. HA molecules promote the osmotic adjustment ability, increase leaf water retention, as well the photosynthetic and antioxidant metabolism of plants under drought stress [74,75]. The integration of HA application and a water deficit makes it possible to assess the precision and efficiency of the system in researching the effect of HA on drought tolerance [45,76].…”
Section: Discussionmentioning
confidence: 99%
“…•− and H 2 O 2 in the leaves of millet; however, HA application reduced the production rate of oxygen radicals along with the decreased activity of SOD and POD. Without the regulation of antioxidant enzymes, HA showed its effect on stomatal conductance, photosystem I and photosystem II activity which improved the photosynthetic performance while also helping to decrease ROS production and maintain membrane stability [94]. The effect of PGPB and HA was examined in drought-affected sugarcane.…”
Section: Droughtmentioning
confidence: 99%
“…Similarly, in the present study, a significant decline in the synthesis of chlorophyll pigments was observed in all Brassica cultivars (Table 1). This might be due to the increased activity of chlorophyllase enzyme, oxidative-breakdown of pigments, thylakoidal membrane distortion, and nutrients deficiency (Shen et al, 2020). The activity of protochlorophyllid reductase was suppressed and chlorophyll synthesis could be reduced upon F I G U R E 4 (A) Net photosynthesis rate (Pn), (B) stomatal conductance to water (Gs), (C) intercellular CO 2 intake (Ci), and (D) transpiration rate (Tr) of B. napus cultivars under drought stress.…”
Section: Tolerant Cultivars Showed Enhanced Activities Of Antioxidative Enzymesmentioning
confidence: 99%